2021
DOI: 10.3389/feduc.2021.614181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Educational Services in Canadian Children With Attention-Deficit/Hyperactivity Disorder

Abstract: The COVID-19 pandemic led to school closures and a rapid transition to online classes. However, little is known about the impact of online learning in Canadian children with Attention-Deficit/Hyperactivity Disorder (ADHD). An online survey created on Qualtrics was distributed to families across Canada. Data collection was conducted over a total of five weeks in May and June 2020. We reviewed 587 surveys (4% margin of error using a 95% confidence interval) completed by caregivers/parents of children with ADHD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In a survey completed by 238 parents of children with SEN in the United Kingdom (Greenway and Eaton-Thomas 2020), 68% reported receiving educational resources from their school, with just over half indicating that the resources were not appropriate for their child's needs, a finding echoed by Garbe et al (2020) conducting research in the United States. For some students, including those with ADHD, parents reported significant challenges for their child in engaging with virtual classes, particularly in terms of executive functioning, staying focused, and avoiding environmental distractions (Hai et al 2021). Designing and implementing remote learning options in inclusive ways that reflect differentiation and alignment with the goals and supports required through students' individual education plans is a significant challenge for educators and school systems, particularly given the rapid changes that many have had to make in response to public safety measures.…”
Section: Engagement In Remote Learning Optionsmentioning
confidence: 99%
“…In a survey completed by 238 parents of children with SEN in the United Kingdom (Greenway and Eaton-Thomas 2020), 68% reported receiving educational resources from their school, with just over half indicating that the resources were not appropriate for their child's needs, a finding echoed by Garbe et al (2020) conducting research in the United States. For some students, including those with ADHD, parents reported significant challenges for their child in engaging with virtual classes, particularly in terms of executive functioning, staying focused, and avoiding environmental distractions (Hai et al 2021). Designing and implementing remote learning options in inclusive ways that reflect differentiation and alignment with the goals and supports required through students' individual education plans is a significant challenge for educators and school systems, particularly given the rapid changes that many have had to make in response to public safety measures.…”
Section: Engagement In Remote Learning Optionsmentioning
confidence: 99%
“…During school closures, the demands on executive skills have most likely increased as DL requires the child to plan his/her own schoolwork to a much greater extent compared to normal schooling, to maintain attention even though the teacher is only shown on the screen or not at all, and to inhibit the home-environmental distractions during online lessons. In line with this, Hai et al ( 19 ) found significant associations between EF deficits and difficulties adjusting to DL. However, these results are limited to children with Attention Deficit Hyperactivity Disorder (ADHD).…”
Section: Introductionmentioning
confidence: 61%
“…In relation to parental educational level, we expected lower parental education to be linked to more negative effects of DL for both parents and their children ( 12 , 24 ). In terms of child factors, we expected that EF deficits would be associated with DL-related negative outcomes for the child ( 19 ). In terms of parent factors, parents' psychological well-being would primarily be related to less DL-related negative outcomes on parents ( 23 ) and to positive effects of DL on family ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the results analysis found, the valuation of students with ADHD was significantly worse for the distance learning project compared to typical students [41]. Similarly, a survey of parents of students with ADHD in Canada found that 41% of a sample of 587 parents stated that their child was unable to successfully meet the needs of tele-education, a figure that should be considered particularly high [42]. Therefore, it seems that independent research leads to the identification of significant obstacles to the participation of students with ADHD in the project of distance learning during the pandemic.…”
Section: The Effect On Students With Adhdmentioning
confidence: 90%